2020
DOI: 10.14780/muiibd.854410
|View full text |Cite
|
Sign up to set email alerts
|

Kahramanmaraş Sütçü İmam Üni̇versi̇tesi̇ Li̇sans Öğrenci̇leri̇ni̇n Fi̇nansal Okuryazarlik Durumlarinin Tespi̇ti̇ne Yöneli̇k Bi̇r Alan Çalişmasi

Abstract: faydalı olacağı düşünülmektedir. Ayrıca yazında yer alan anketlerin geniş bir şekilde harmanlanması ve nicelik olarak iyi düzeyde değerlendirilebilecek bir örneklem üzerinden alan araştırmasının yürütülmesi, çalışmanın özgünlüğünü ve pratik uygulamalara ön ayak olma potansiyelini ortaya koymaktadır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These findings are in parallel with our results. In the studies conducted by Contuk (2018) and Engin et al (2020), significant differences were found in education types. It was concluded that morning class students had higher averages than evening class students.…”
Section: The Hypothesis "(H3)mentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are in parallel with our results. In the studies conducted by Contuk (2018) and Engin et al (2020), significant differences were found in education types. It was concluded that morning class students had higher averages than evening class students.…”
Section: The Hypothesis "(H3)mentioning
confidence: 97%
“…It is thought that the reason for reaching a different result from our study is due to the region, university, or diverse student group where the study was conducted. On the other hand, Jorgensen and Savla (2010), Cull andWhitton (2011), Ludlum, Tilker, Ritter, Cowart, andXu (2012), Adeleke (2013), Thapa (2015), Rosacker and Rosacker (2016), Barış (2016), Biçer (2016), Yücel and Çiftçi (2018), Karadeniz, Koşan, Geçgin, and Beyazgül (2019), Aydın and Selçuk (2019), Engin, Eren, and Balkar (2020), Uyar and Atalay (2021), and Onat and Yöntem (2022) reported no statistically significant difference between male and female individuals.…”
Section: The Hypothesis Of "(H1)mentioning
confidence: 99%